2017
DOI: 10.14687/jhs.v14i2.4320
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dispareunia in women within postpartum one-year period and related factors

Abstract: This study aimed to determine prevalence of postpartum dyspareunia and related factors.In cross-sectional and descriptive study, a questionnaire was used to collect data. Universe of the study was composed of all women in the first postpartum one year, Sampling consisted of 246 women in postpartum one-year period admitted to public healtcare centers in Konya, Turkey.While the rates of experiencing dispareunia were 20.8% in prenatal period, 22.9% during pregnancy and 36.6% in the first intercourse after deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Quality sleep and rest support SQOL, and a healthy sex life also contributes to quality sleep and rest 62 . For example, in a study conducted with climacteric women, women with high fatigue were found to have low SQOL 63 . In this study, we also observed a strong negative relationship between fatigue level and SQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Quality sleep and rest support SQOL, and a healthy sex life also contributes to quality sleep and rest 62 . For example, in a study conducted with climacteric women, women with high fatigue were found to have low SQOL 63 . In this study, we also observed a strong negative relationship between fatigue level and SQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Many low-and middle-income countries in East Asia, Southeast Asia, the Middle East, Latin America, and Africa follow local traditions for postpartum care after childbirth, such as restricting maternal activities, limiting diet, staying warm, and relying on family members, among other traditional practices [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%